Cascade Delivery to Golgi Apparatus and On‐Site Formation of Subcellular Drug Reservoir for Cancer Metastasis Suppression (Small 11/2023). Issue 11 (15th March 2023) - Chen, Liqiang; Jiang, Peihang; Shen, Xinran; Lyu, Jiayan; Liu, Chendong; Li, Lian; Huang, Yuan
Abstract : Cancer Metastasis Suppression In article number 2204747, Yuan Huang and co‐workers develop a strategy that enhances the targetability and retention of nano‐drug in Golgi apparatus (GA) for cancer metastasis suppression. Hybrid cell membrane‐coated nanoparticles cascade to delivering cargo into GA, and in return, loaded‐Monensin, an exocytosis inhibitor, blocks nano‐drug exocytosis like steel net. With GA retention of nano‐drug and GA dysfunction, this strategy suppresses metastasis initialization via multiple GA‐related pathways.